Design and synthesis of compounds that extend yeast replicative lifespan - Yang, Hongying (2006)
This past decade has seen the identification of numerous conserved genes that extend lifespan in diverse species, yet the number of compounds that extend lifespan is relatively small. A class of compounds called STACs, which were identified as activators of Sir2/SIRT1 NAD(+)-dependent deacetylases, extend the lifespans of multiple species in a Sir2-dependent manner and can delay the onset of age-related diseases such as cancer, diabetes and neurodegeneration in model organisms. Plant-derived STACs such as fisetin and resveratrol have several liabilities, including poor stability and relatively low potency as SIRT1 activators. To develop improved STACs, stilbene derivatives with modifications at the 4′ position of the B ring were synthesized using a Horner-Emmons-based synthetic route or by hydrolyzing deoxyrhapontin. Here, we describe synthetic STACs with lower toxicity toward human cells, and higher potency with respect to SIRT1 activation and lifespan extension in Saccharomyces cerevisiae. These studies show that it is possible to improve upon naturally occurring STACs based on a number of criteria including lifespan extension.